Navigating intercultural competence at home. - Schembri, Sharon (Journal of University Teaching & Learning Practice v.21 n.4 https://doi.org/10.53761/1m378720, 2024)
A globalised world brings diversity into the classroom and internationalisation to higher education, where intercultural competence comes to the fore. Accommodating interculturality, however, extends beyond the international student cohort and includes heterogeneous domestic cultures, including Indigenous cultures. In the Australian context, historically Aboriginal and Torres Strait Islander peoples have experienced limited access to culturally appropriate health, social and educational services. Accordingly, higher education institutions can be vehicles of change in this regard. More specifically, just as many higher education providers have moved towards internationalised curriculum, there is increasing evidence and intention to introduce Indigenised curriculum where respective educators delivering indigenised curricula need to be culturally competent. Institutions therefore, are offering cultural training programs for educators delivering Indigenised curricula, where recognition of Indigenous cultural competence amongst educators would be useful. Yet, the review presented in this paper demonstrates a gap in literature regarding measurement of cultural and intercultural competence in the context of Australian higher education. To that end, an instrument specifically designed to measure educator intercultural competence in Australia as related to Aboriginal and Torres Strait Islander peoples is proposed. This instrument will enable higher education institutions to document educator Indigenous cultural competence, demonstrate the intercultural skills of their educational staff and continuously improve intercultural competency within the institution. [Author abstract]